Benim adım kırmızı - Pamuk, Orhan 1952- (İletişim, 1998)
"When the Sultan commissions a great book to celebrate his royal self and his extensive dominion, he directs Enishte Effendi to assemble a cadre of the most acclaimed artists in the land. Their task: to illuminate the work in the European style. But because figurative art can be deemed an affront to Islam, this commission is a dangerous proposition indeed, and no one in the elite circle can know the full scope or nature of the project." "Panic erupts when one of the chosen miniaturists disappears, and the Sultan demands answers within three days. The only clue to the mystery - or crime? - lies in the half-finished illuminations themselves. Has an avenging angel discovered the blasphemous work? Or is a jealous contender for the hand of Enishte's ravishing daughter, the incomparable Shekure, somehow to blame?"
Keywords: Illumination of books and manuscripts / Fiction; Islam and art / Fiction; Historical fiction; Istanbul (Turkey) / Fiction; Fiktionale Darstellung